High risk of post‐infectious irritable bowel syndrome in patients with Clostridium difficile infection. Issue 6 (22nd July 2016) - Wadhwa, A.; Al Nahhas, M. F.; Dierkhising, R. A.; Patel, R.; Kashyap, P.; Pardi, D. S.; Khanna, S.; Grover, M.
Summary: Background: Infectious enteritis is a commonly identified risk factor for irritable bowel syndrome (IBS). The incidence of Clostridium difficile infection (CDI) is on the rise. However, there is limited information on post‐infectious IBS (PI‐IBS) development following CDI and the host‐ and infection‐related risk factors are not known. Aim: To determine the incidence and risk factors for PI‐IBS following CDI. Methods: A total of 684 cases of CDI identified from September 2012 to November 2013 were surveyed. Participants completed the Rome III IBS questionnaire and details on the CDI episode. Predictive modelling was done using logistic regression to evaluate risk factors for PI‐IBS development. Results: A total of 315 CDI cases responded (46% response rate) and 205 were at‐risk (no pre‐CDI IBS) for PI‐IBS development. A total of 52/205 (25%) met the Rome III criteria for IBS ≥6 months following CDI. IBS‐mixed was most common followed by IBS‐diarrhoea. In comparison to those without subsequent PI‐IBS, greater percentage of PI‐IBS patients had CDI symptoms >7 days, nausea, vomiting, abdominal pain during CDI, anxiety and a higher BMI. Using logistic regression, CDI symptoms >7 days [Odds ratio (OR): 2.96, P  = 0.01], current anxiety (OR: 1.33, P  < 0.0001) and a higher BMI (OR: 1.08, P  = 0.004) were independently associated with PI‐IBS development; blood in the stool during CDI was protective (OR: 0.44, P  = 0.06). Conclusions: In this cohort study, new‐onset IBS is common after CDI. Longer CDI duration, current anxiety and higher BMI are associated with the diagnosis of C. difficile PI‐IBS. This chronic sequela should be considered during active management and follow‐up of patients with CDI.